Implementing psychosocial interventions for teachers' mental health: Protocol for integrating scoping review with teachers lived experiences in LMICs. - Kanika Malik; Sadananda Reddy; Yasmine A Shilla; Aditi Khanna; Ranya R Kaurr; Abbey Boban (PLoS ONE)
Introduction Teachers are pivotal in shaping educational environments and student development but face significant occupational stress and high rates of mental problems. Despite the availability of various psychosocial interventions, comprehensive evidence of their effectiveness and implementation is limited for this occupational group, especially in low- and middle-income countries (LMICs). This mixed methods study aims to conduct a scoping review of characteristics, effectiveness, and implementation outcomes of psychosocial interventions for teachers' mental health and mental problems, integrating these with teachers' lived experiences to inform the implementation of mental health interventions in LMICs. Methods The study combines a scoping review with insights from an advisory group of teaching professionals with relevant lived experiences (PWLEs). The review will focus on examining psychosocial interventions studies promoting mental health or addressing mental problems among grade 1-12 school teachers of all genders, ages and contexts, except those working in specialized settings, such as special education centers, or disaster- or crisis-stricken zones. Intervention studies exclusively focusing on physical health or job-related outcomes will be excluded. Using pre-defined search terms, quantitative and qualitative research studies, including unpublished literature, will be searched across multiple databases. Titles and abstracts of identified studies will be screened against inclusion criteria, and the potentially relevant sources will be retrieved in full. Data will be extracted using a data extraction sheet developed for the study covering variables related to participant characteristics, intervention characteristics, study context, effectiveness and implementation outcomes. A purposively selected sample of 10 PWLEs will form the study advisory group and participate in four online workshop-group discussions. The meetings will include a presentation of the scoping review findings, followed by discussions on the relevance of these intervention packages for LMICs, adaptations needed to make them acceptable among school teachers and feasible for delivery in low-resourced settings like India. The synthesis of the data will employ narrative and thematic approaches to generate actionable insights for implementing psychosocial interventions in LMICs. Discussion This study will provide comprehensive evidence on the characteristics and outcomes of psychosocial interventions for teachers' mental health and mental problems. By integrating insights from teachers with relevant lived experiences, the study will provide practical guidelines for adapting and implementing psychosocial interventions among school teachers in LMICs. Trial registration Review registration number: Open Science Framework, doi.org/10.17605/OSF.IO/GF59J.